Answer:
(1/4 + 5/4)^2 +3/4 = 12
Explanation:
To solve the problem given, we will follow the steps below;
(1/4 + 5/4)^2 +3/4
First, we will find the value of (1/4 + 5/4)^2
1/4 + 5/4 = 6/4
(1/4 + 5/4)^2 = (6/4)^2 =
![(36)/(16)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/p1klfo1exprbajnjamkec1t0w443zsjsix.png)
can be reduced to
![(9)/(4)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/mu5wv2sdrs8r07ck3s3v4c71inoihz0ih9.png)
This implies that ; (1/4 + 5/4)^2 =
![(9)/(4)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/mu5wv2sdrs8r07ck3s3v4c71inoihz0ih9.png)
Then, we can now add
and
together
(1/4 + 5/4)^2 +3/4 =
+
=
= 4
Therefore (1/4 + 5/4)^2 +3/4 = 12